Carcinosarcoma of pancreas: an unusual pancreatic tumour: case report - A., Anandi; P. A., Praveen; R., Rani Suganya (International Surgery Journal, 2023)
Carcinosarcoma of pancreas is a rare tumour with limited clinical and pathological data reported in literature. Although carcinosarcoma predominantly found in uterus, it has been identified in breast, liver, prostate, kidney, salivary glands and pancreas. Carcinosarcoma is a biphasic tumour with epithelial and mesenchymal components. About less than 40 cases had been reported in literature. The treatment of choice in most reported cases is surgery. Given such rarity, we report a case of pancreatic carcinosarcoma diagnosed in our institution, review tumour clinicopathological characteristics, and describe our surgical and medical management strategy.